-c=-2c-6

Simple and best practice solution for -c=-2c-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -c=-2c-6 equation:


Simplifying
-1c = -2c + -6

Reorder the terms:
-1c = -6 + -2c

Solving
-1c = -6 + -2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '2c' to each side of the equation.
-1c + 2c = -6 + -2c + 2c

Combine like terms: -1c + 2c = 1c
1c = -6 + -2c + 2c

Combine like terms: -2c + 2c = 0
1c = -6 + 0
1c = -6

Divide each side by '1'.
c = -6

Simplifying
c = -6

See similar equations:

| 5x(-7)=(-35) | | 6-7w=-4-10w+8w | | 0.35*0.43= | | 77.0=3900(t) | | (7/9)d=14/3 | | 4+7u=6u-2 | | 12(x)+16(y)=232 | | 20*(3x)=12-x | | 3x-12=3+2x | | 65-35=3.4(a) | | ((5x^7y)/(6a^-1b^-9))^-1 | | (65.0mph-35.0mph)=3.4(a) | | 5x+3y=5-6 | | 40-(3x)=12-x | | p+0.06p=1.06p | | 5x+3y=5-6i | | 8x^2-4x=4 | | 20+(3x)=24-x | | 4.5-1.5(6m+2)= | | 5r^2-8r=3 | | 10d+7=1+9d | | (3a^2)b= | | X+3X-4=6-2 | | 6x^4=0 | | 9x-2457=5x-160 | | -39+x=5x+7(x+7) | | -5=3/4x-2 | | r^2=16+9 | | 8d+18-d=d | | 65=35+a(3.4) | | 32+(3x)=12-x | | ny-6+y+8=42 |

Equations solver categories